Gene expression profiles and in vitro development following vitrification of pronuclear and 8-cell stage mouse embryos - Duangjai Boonkusol (2018)
The analysis of differences in gene expression, responding to cryopreservation may explain some of the observed differences in further development of the preimplantation stage embryos. The aim of this study was to create a link, for the first time, between morphological/developmental observations and gene activity changes following cryopreservation of embryos. Efficiency of two vitrification methods, solid surface and in-straw vitrifications for pronuclear-stage mouse zygotes and 8-cell stage mouse embryos was compared based on morphological survival, blastocyst formation, and changes in embryonic gene expression. Both stages of embryos were vitrified by SSV using 35% ethylene glycol (EG) for vitrification solution (VS) and in-straw vitrification using 40% EG for VS. No significant differences were found between immediate survival rates of embryos vitrified by SSV and in-straw vitrification in both stages. Blastocyst rates were significantly higher with SSV and not significantly different from that of control. These results showed that SSV was more efficient than in-straw vitrification. Treatment with cytochalasin-b did not improve cryosurvival during SSV. The quantification of selected gene transcripts from single embryo (6 embryos/treatment group) were carried out by quantitative real-time RT-PCR. It was performed by adding 1/8 of each embryo cDNA to the PCR mix containing the specific primers to amplify housekeeping gene (β-actin), heat shock protein gene (Hsp70), genes related to oxidative stress (MnSOD and CuSOD), cold stress (CirpB, Rbm3), and cell-cycle arrest (Trp53). We found upregulation of all six stress-related genes at 3 hr post-warming in pronuclear stage embryos. Expression of these genes showed much higher level (2-33-fold) in in-straw vitrification than in in vitro control embryos. In SSV-treated embryos we could detect only slight changes (0.3-2-fold). At 10 hr post-warming, all genes were downregulated in embryos vitrified by in-straw method. In SSV-treated group expression of Hsp70 showed slight increase and Trp53 showed decrease. In contrast to pronuclear stage, there was no clear pattern of gene expression changes after vitrification in 8-cell stage embryos. Several genes were upregulated both at 3 and 10 hr post-warming. Moreover, we found upregulation of β-actin gene which we expected to use as a reference gene in in-straw treated embryos in both 3 and 10 hr post-warming, while in pronuclear stage embryos and in SSV treatment there was no effect on β-actin expression level. There was no difference in gene expression between blastocysts developed from fresh or vitrified embryos. In conclusion, the real-time RT-PCR method from single embryo opened new opportunities for the understranding of molecular events following cryopreservation. The upregulation of stress-related genes at 3 hr post-warming in pronuclear stage embryos might have been an early indicator of reduced viability following in-straw vitrification in good correlation with the developmental data to blastocyst stage. © 2006 Wiley-Liss, Inc.